Children use of emergency care: Differences between natives and migrants in Italy - Elena Cottini; Claudio Lucifora; Gilberto Turati; Daria Vigani (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2020)
In this paper we study the differences between natives and migrants in the appropriate use of emergency care. We focus on children under one year of age using a sample of more than 45,000 children living in the Metropolitan area of Milan. Consistently with the literature, our findings show that migrants' children are characterized both by a higher probability to use emergency care and by a higher likelihood of an inappropriate use of this service. These findings are robust to the inclusion of additional controls, family doctor's characteristics, as well as potential selection bias. We also explore potential mechanisms driving these results. We find that linguistic and cultural distance between natives and migrants explain the higher use of emergency services and the inappropriate use of these services. Conversely supply side factors do not seem to play any relevant role. These findings suggest that integration policies aimed at increasing language proficiency of immigrants would be helpful in improving the appropriate use of emergency care.
Keywords: I10; I14; J15; 330; emergency care; children; migrants; inappropriate care